DETERMINACIÓN DE LA SEROPREVALENCIA DE TOXOPLASMOSIS EN ALPACAS Y LLAMAS EN LA ESTACIÓN EXPERIMENTAL INIA-PUNO - Gómez O., Felices (2003)
The objective of this study was to determine the seroprevalence of Toxoplasma gondii in alpacas and lamas from the experimental station of INIA-Puno (Quimsachata), located in the Lampa province, Puno. For this purpose, 200 alpacas and 136 lamas, both male and female, were sampled in June 2000. Blood serum was collected to detect antibodies by the indirect haemaglutination test (IHA). 44.5 ± 6.9% (89/200) of alpaca samples had antibodies. Seroprevalence found in females (56.0 ± 9.7%) was higher than that in males (33.0 ± 9.2%) (p<0.01). Seroprevalence increased with age (p<0.01). The seroprevalence in lamas was 27.9 + 7.5% without differences between sexes, but increasing with age (p<0.01). The results showed a seroprevalence relatively higher in alpacas than in lamas at the INIA-Puno station. It was found that sex is a risk factor for acquiring toxoplasmosis in alpacas, but not in lamas, and age is a risk factor for the infection with T. gondii for both alpacas and lamas (p<0.01).